Predictive Value of Acute Phase Proteins for the Short-Term Outcome of Meningoencephalitis of Unknown Origin in Dogs - Aurora Cocchetto; Andrea Zoia; Rita Aragão; Laura Ventura; Marika Menchetti (Animals, 2023)
Meningoencephalitis of unknown origin (MUO) is one of the most common inflammatory diseases of the central nervous system (CNS). The study evaluates the possible increase and the potential role of acute phase proteins (APPs) and other inflammatory serum parameters as biomarkers predicting the short-term outcome of dogs with meningoencephalitis of unknown origin (MUO). A retrospective cohort study was designed. The APP profile and other markers of systemic inflammation of forty-eight client-owned dogs with a new diagnosis of MUO were compared between 7-day survival and non-survival dogs diagnosed with MUO. Thirty-nine (81%) dogs were alive at the end of the 7-day follow-up period, while 9 (19%) dogs died or were euthanized because of MUO. None of the 11 markers of inflammation studied were different between the survived and non-survived dogs; for this reason, none of them could be used as a predictor of the short-term outcome based on the results of the present study. This confirms that even though MUO is often associated with a severe inflammatory status of the central nervous system (CNS), this condition is probably isolated exclusively to the CNS.